A review on magnetic and spintronic neurostimulation: challenges and prospects. (30th April 2022) - Saha, Renata; Wu, Kai; Bloom, Robert P; Liang, Shuang; Tonini, Denis; Wang, Jian-Ping
Abstract: In the treatment of neurodegenerative, sensory and cardiovascular diseases, electrical probes and arrays have shown quite a promising success rate. However, despite the outstanding clinical outcomes, their operation is significantly hindered by non-selective control of electric fields. A promising alternative is micromagnetic stimulation ( μ MS) due to the high permeability of magnetic field through biological tissues. The induced electric field from the time-varying magnetic field generated by magnetic neurostimulators is used to remotely stimulate neighboring neurons. Due to the spatial asymmetry of the induced electric field, high spatial selectivity of neurostimulation has been realized. Herein, some popular choices of magnetic neurostimulators such as microcoils ( μ coils) and spintronic nanodevices are reviewed. The neurostimulator features such as power consumption and resolution (aiming at cellular level) are discussed. In addition, the chronic stability and biocompatibility of these implantable neurostimulator are commented in favor of further translation to clinical settings. Furthermore, magnetic nanoparticles (MNPs), as another invaluable neurostimulation material, has emerged in recent years. Thus, in this review we have also included MNPs as a remote neurostimulation solution that overcomes physical limitations of invasive implants. Overall, this review provides peers with the recent development of ultra-low power, cellular-level, spatially selective magnetic neurostimulators of dimensions within micro- to nano-range for treating chronic neurological disorders. At the end of this review, some potential applications of next generation neuro-devices have also been discussed.